Energy Efficiency Solutions for Historic Buildings. A Handbook - Bastian, Zeno (Birkhäuser - an imprint of De Gruyter, 2015)
This handbook holistically summarises the principles for the energy retrofitting of historic buildings, from the first diagnosis to the adequately designed intervention: preservation of the historic structure, user comfort, and energy efficiency. The content was developed by an interdisciplinary team of researchers. The wide range of different expertise, design examples, calculations, and measuring results from eight case studies makes this manual an indispensable tool for all architects, engineers, and energy consultants.